Designing a Mobile Game Based on Augmented Reality Application for Learning Media - Antonius Suratno; Erdhi Widyarto Nugroho (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
Designing games for educational purposes needs to consider various aspects that help lead to the making of a good game. This study aims to describe users’ responses towards the potential of the game for blended learning, the design stages and the trial which encompass pre-design input taking, design stages, trial, and evaluation. The inputs from the pre-design stage have been the basis for the media design; the trial stage inputs from the prospective users and two experts provide feedback for the validity of media both in content and construct aspects. The research subjects involved 100 Junior high school students, 5 English language teachers, and 1 game design expert. The tools of data collection are questionnaire and semi-structured interview which were developed by the researchers. The intended subject for which this game is designed is reading comprehension and the study is planned to be conducted in approximately eight months. Both types of feedback were used to evaluate the readiness of the media for the real use for blended learning model. The results showed that the validity in content and construct aspects were both very good. The trial result also suggests that the game is considered a decent product, attractive and easy to use for independent learning. Thus, the final evaluation suggests that the media is readily usable for the real context of blended learning.